2016
DOI: 10.1002/mbo3.395
|View full text |Cite
|
Sign up to set email alerts
|

Lysis‐lysogeny coexistence: prophage integration during lytic development

Abstract: The infection of Escherichia coli cells by bacteriophage lambda results in bifurcated means of propagation, where the phage decides between the lytic and lysogenic pathways. Although traditionally thought to be mutually exclusive, increasing evidence suggests that this lysis‐lysogeny decision is more complex than once believed, but exploring its intricacies requires an improved resolution of study. Here, with a newly developed fluorescent reporter system labeling single phage and E. coli DNAs, these two disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…Using the ParB/parS system, researchers observed that in lysogenic cells, the bacterial attB locus migrated toward the largely stationary phage DNA over time to possibly facilitate integration (62). A similar behavior was observed using the SeqA-FP system to label lambda DNA and a tetO/TetR system to label bacterial attB in lysogenic cells (37). Even in lytic cells, attB generally converges with lambda DNA-rich regions in an integrase-independent manner, leading to more co-localization of attB and lambda DNA (37).…”
Section: Biophysical Properties Of Phages In Vivomentioning
confidence: 65%
See 2 more Smart Citations
“…Using the ParB/parS system, researchers observed that in lysogenic cells, the bacterial attB locus migrated toward the largely stationary phage DNA over time to possibly facilitate integration (62). A similar behavior was observed using the SeqA-FP system to label lambda DNA and a tetO/TetR system to label bacterial attB in lysogenic cells (37). Even in lytic cells, attB generally converges with lambda DNA-rich regions in an integrase-independent manner, leading to more co-localization of attB and lambda DNA (37).…”
Section: Biophysical Properties Of Phages In Vivomentioning
confidence: 65%
“…Methylated phage DNA was tracked by the binding of SeqA-FP, and E. coli DNA was labeled at the attB (the lambda DNA integration site) locus with an inserted tetO array being bound by TetR-FP. Combined with cell-fate reporter systems, lambda DNA integration indicative of the lysogenic pathway was observed for lytic cells (37). This suggests that subcellular phage entities show a degree of individuality and can behave differently from each other.…”
Section: Phage Voting For Decisionsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is possible that prophage is not able to stably integrate during the infection, the prophage-SAR11 genome coexistence is temporary in order to keep host genome streamlined. Recently, a “lyso-lysis” phenomenon was observed in bacteriophage lambda, where phage integration was followed by a lytic life cycle (61) and the frequency of lyso-lysis increases with the number of infecting phages. Even this bacteria-phage genome coexistence is likely temporary, still provides a window for evolution of mutually benefical functions (62).…”
Section: Resultsmentioning
confidence: 99%
“…When environmental conditions are favorable, e.g., abundant host cells living in copiotrophic conditions, the lytic cycle is preferred, but when hosts are scarce, the infecting phages may decide for the lysogenic cycle (Oppenheim et al, 2005;Zeng et al, 2010;Koskella and Brockhurst, 2014;Obeng et al, 2016). If phage concentration inside the cell is high enough phages will decide for the lysogenic cycle (Zeng et al, 2010;Shao et al, 2017). As shown recently (Erez et al, 2017), phages may have sophisticated mechanisms for sensing host abundance.…”
Section: A Symbio-centric Ecological Speciation Frameworkmentioning
confidence: 99%